(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this work, the possibility of usage of lignocellulosic biomass derived from wood processing wastewater as an environmentally friendly dust suppressant was studied. To increase the efficiency of the recovery of lignocellulosic biomass, a new developed composite coagulant, representing a polymer-colloid complex of polyethyleneimine with polyvalent metal ions, was applied. The effectiveness of the composite coagulant was examined using a model solution simulating the wastewater of hydrothermal treatment of birch wood. The optimum content of PEI in the composite coagulant was found to be 25-35%. At the optimal composite coagulant dosage and pH value, the yield of the total wood biomass achieved 97%, but the extraction of lignin and lignin-like substances was more than 65%. Due to the polymeric and polyfunctional nature, the recovered wood biomass had glue properties. Taking into account the fact that the dust at the surface of unpaved roads poses considerable environmental problems, the biomass was tested as a structuring agent for sandy and model sandy-clay soils. The obtained results have shown that the separated lignocellulosic biomass was capable of forming large sandy aggregates that were able to decrease the dusty soil blowing off from the unpaved road surface.